The Moderating Role of Policy Intervention on the Relationship of Environment, Social, and Governance (ESG) and Cost of Equity Capital: A Study in Basic Materials Companies in Asia - Yanthi Hutagaol-Martowidjojo; Valentina Tohang; Emmanuella P.T. Payung (Australasian Accounting, Business and Finance Journal, 2023)
Environment, Social, and Governance (ESG) disclosure is a non-financial disclosure that is expected to enhance firms’ transparency, ease estimation of risk, hence lower cost of equity (CoE). However prior studies show mixed results. Using Institutional theory, this paper argues that sustainability policy intervention could have a different effect. However, this framework expects that the more ESG disclosure, the higher firms’ cost of equity (CoE) due to shareholders’ perception of mindless ESG plan. The policy intervention examined is government regulation of mandatory sustainability practices. This study uses a sample of 98 basic materials sector companies in eleven Asia countries with 5 years study period from 2017-2021 as a research sample. Using panel-data regression analysis, this study finds that there is a positive relationship between ESG scores and CoE. Moreover, the government policy strengthens such a relationship. Therefore, consistent with coercive mechanism in institutional theory, we conclude that mandatory sustainability disclosure in the Asian Basic material sector companies in-creases firms’ CoE and the existence of mandatory regulation strengthens such a relationship.
Keywords: SDG 17; Basic material industry; Cost of Equity; ESG disclosure; Institutional theory; Sustainable policy intervention